Physical therapist assistant - Quinlan, Kathryn A. (Mankato, Minn. : Capstone High/Low Books, 1998)
Outlines the educational requirements, duties, salary, employment outlook, and possible future positions of physical therapy assistant.
Includes bibliographical references (p. 45-47) and index.
Keywords: Physical therapy assistants -- Juvenile literature. -- Juvenile literature; Physical therapy assistants; Vocational guidance